(untitled) (African Journal of Biomedical Research, 2022)
BACKGROUND: Maternal glucocorticoid administration during lactation has an effect on metabolic imbalance. This study examine the effect of Allium cepa Lin on maternal dexamethasone-induced alteration in lipid profile and oxidative stress in the liver of the male offspring of Wistar rats. METHODS: Twenty female Wistar rats were divided into four groups (n=5) during lactation. Group 1 was administered subcutaneously 0.05ml/kg/day normal saline from days 1-21. Group 2 was administered 30% onion mixed diet from lactation days 1-21. Group 3 was administered subcutaneously 100µg/kg/day dexamethasone from lactation days 1-21. Group 4 was administered subcutaneously 100µg/Kg/day dexamethasone (dex) for 21 days + 30% onion mixed diet throughout lactation. RESULTS: Results from this study showed that dexamethasone treatment during lactation significantly (p<0.05) reduced the body weight, HDL-cholesterol, hepatic catalase and SOD activities of the male offspring. There was also a significant (p<0.05) increase in hepatic MDA, total cholesterol, LDL-cholesterol and TAG when compared with the control. Meanwhile maternal exposure to dexamethasone and 30% onion mixed diet significantly (p<0.05) raised the serum HDl-cholesterol level, Hepatic SOD and catalase activities. The serum LDL-cholesterol, total cholesterol and TAG were reduced in the male offspring when compared with the dexamethasone only treated group. CONCLUSION: Findings from this study suggest that maternal consumption of 30% onion mixed diet may ameliorate the metabolic alterations induced in the male offspring following maternal treatment with dexamethasone during lactation in Wistar rats.